2012
DOI: 10.1111/j.1600-0781.2012.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin‐induced phototoxicity in an adult cystic fibrosis population

Abstract: The incidence of phototoxicity as a side effect of ciprofloxacin appears to be increased in patients with cystic fibrosis compared to the general population (approximately 2.4%). We used an interview-based questionnaire to determine the incidence of such phototoxic skin reactions in cystic fibrosis patients. Results from 105 respondents revealed the incidence of ciprofloxacin-induced phototoxicity in the adult cystic fibrosis population in Northern Ireland to be 48.4% with only 66% of the patients recalling be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…on patients presenting with drug‐induced skin adverse reactions, photosensitivity was the third commonest cause. In specialized photodiagnostic units, systemic drug‐induced photosensitivity is reported to account for up to 15% of photodermatoses . However, these cases only represent those actually referred for investigation of suspected photosensitivity and as such do not reflect the true incidence …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…on patients presenting with drug‐induced skin adverse reactions, photosensitivity was the third commonest cause. In specialized photodiagnostic units, systemic drug‐induced photosensitivity is reported to account for up to 15% of photodermatoses . However, these cases only represent those actually referred for investigation of suspected photosensitivity and as such do not reflect the true incidence …”
Section: Discussionmentioning
confidence: 99%
“…In specialized photodiagnostic units, systemic drug-induced photosensitivity is reported to account for up to 15% of photodermatoses. [20][21][22][23][24][25] However, these cases only represent those actually referred for investigation of suspected photosensitivity and as such do not reflect the true incidence. 10 Up to the present, a large quantity of drugs has been associated with photosensitivity and this number is increasing constantly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…observed that the maximum transient absorption at 610 nm is the 3 CPX * (30). Evidence has shown that CPX can efficiently cause damage to DNA in vivo (6,7), which may be due to the formation of reactive oxygen species (ROS) such as O 2 · , 1 O 2 , · OH and H 2 O 2 (8,31,32).…”
Section: Introductionmentioning
confidence: 99%